2000
DOI: 10.1021/ja9930014
|View full text |Cite
|
Sign up to set email alerts
|

Solution Conformations of Helix-Forming β-Amino Acid Homooligomers

Abstract: The conformational properties of β-peptides comprised of enantiomerically pure trans-2-aminocyclohexanecarboxylic acid (ACHC) or trans-2-aminocyclopentanecarboxylic acid (ACPC) units were studied by NMR spectroscopy in organic solvents. In pyridine-d 5 solution, ACPC hexamer 1 and ACPC octamer 2 displayed well-defined helical structures characterized by a series of 12-membered hydrogen-bonded rings (“12-helix”). The solution structures calculated from the NMR-derived constraints were very similar to the confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
2
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 25 publications
9
93
2
2
Order By: Relevance
“…After two hours, saturated aqueous NH 4 Cl solution was added and the resulting solution warmed to r.t., partitioned between DCM (3 x 50 mL) and brine, dried and concentrated in vacuo gave a 3:1 mixture of 17/18 (203 mg, 90%), as deduced by integration of the methyl ester signals in the 1 H-NMR at 3.44 and 3.62 ppm respectively.…”
Section: Preparation Of Methyl (1s2s5sαs)-2-n-benzyl-n-α-methylbenmentioning
confidence: 99%
See 1 more Smart Citation
“…After two hours, saturated aqueous NH 4 Cl solution was added and the resulting solution warmed to r.t., partitioned between DCM (3 x 50 mL) and brine, dried and concentrated in vacuo gave a 3:1 mixture of 17/18 (203 mg, 90%), as deduced by integration of the methyl ester signals in the 1 H-NMR at 3.44 and 3.62 ppm respectively.…”
Section: Preparation Of Methyl (1s2s5sαs)-2-n-benzyl-n-α-methylbenmentioning
confidence: 99%
“…The cis-diastereoisomer shows potent antifungal activity while Fülop et al have recently demonstrated that oligomers of cis-pentacin adopt a sheet type structure in DMSO [1]. Furthermore, Gellman et al have demonstrated that short chain β-peptides derived from trans-pentacin adopt 12-membered helical structures [2][3][4][5] and when a pyrrolidine-base β-amino acid is incorporated into the hexa-β-peptide 3, it confers water solubility when the ring nitrogen is protonated [6][7]. In addition, oligomers composed of the 3-substituted transpentacin residues 4, 5 and 6 fold in water, which should facilitate the design of β-peptides for biological applications (Figure 1) [8].…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43] When a proton is involved in hydrogen bond, its electrons are shared by two electronegative elements and its electron density is hence decreased. Therefore, the proton is deshielded and comes into resonance at a lower field.…”
Section: Hydrogen Bond Analysismentioning
confidence: 99%
“…Like natural peptides and proteins, β-peptides can adopt folded conformations including common secondary structures such as helices [11]- [13] [22]- [28], turns [18] [29] and sheets [14] [30]. Compared to α-peptides, β-peptides have the advantage of increased conformational stability in an aqueous environment.…”
Section: Introductionmentioning
confidence: 99%
“…[15] The β-peptide backbone compared to natural peptides is resistant to protease degradation and has the potential for a great variety of substitution patterns [31]. In addition β-peptides form more stable helices in solution compared to α-peptides; β-peptides can form secondary structures with as few as four to six residues in solution [13] [16] [19], compared to over 30 residues needed for stability of the natural analogs. The stability of β-peptides, important for biological activity, makes them good candidates for useful drugs.…”
Section: Introductionmentioning
confidence: 99%